Understanding UK medical students' perspectives on a career in cardiothoracic surgeryCentral MessagePerspective - Ariana Axiaq, MBBS; Renier A.B. Visser, MBBS; Manasi Shirke, BSc; Arwa Khashkhusha, MBBS; Sara Zaidi, BSc; Raneesha Pillay, BSc; Christopher J. Goulden, BSc; Amer Harky, MRCS, MSc; Hugo Labat; Khubbaib Hasan; Marco Shiu Tsun Leung; Makishaa Nanthakumar (JTCVS Open, 2021)
Objectives: The UK postgraduate training program in cardiothoracic surgery is challenging and competitive, with trainees choosing the field for different reasons. This study aims to identify factors that influence medical students in pursuing a career within cardiothoracic surgery. Methods: A cross-sectional study was carried out in which a questionnaire was anonymously filled out by medical students across 17 medical schools in the United Kingdom. An online survey platform was used for survey distribution and analysis. A mixed-methods approach was employed to gather quantitative and qualitative data. Data collection consisted of a series of closed questions and 1 open-ended question. The questions focused on the attitudes toward, knowledge of, and exposure to cardiothoracic surgery. Results: The survey yielded 265 responses. Interest in cardiothoracic surgery was seen in 45.3% of participants, with the leading factor for pursuing this career being lifestyle factors (50%), closely followed by the career opportunities (42.9%) and the aid of mentors (31%). Some discouraging factors were: Difficulty of learning material (37.7%), length of the training program (27.4%), competition in the field (26%), stress (24.3%), and lifestyle factors (22.1%). Conclusions: Whilst UK medical schools try to provide an introduction to specialties like cardiothoracic surgery, there remains a proportion of medical students who do not have access to opportunities needed to make a balanced career decision. Additionally, individual circumstances and aspirations tend to change from students' first year of study to their final year, which can alter their perceptions about the field.